2020
DOI: 10.1063/5.0010891
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam-induced nanopores in Bernal-stacked hexagonal boron nitride

Abstract: Single-layer h-BN is known to have edges with unique magnetism, however, in the commonly fabricated multilayer AA-h-BN, edge relaxations occur that create interlayer bonds and eliminate the unpaired electrons at the edge. Recently, a robust method of growing the unconventional Bernalstacked h-BN (AB-h-BN) has been reported. Here, we use theoretical approaches to investigate the nitrogen-terminated zigzag edges in AB-h-BN that can be formed in a controlled fashion using a high-energy electron beam. We find that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 86 publications
(108 reference statements)
1
30
0
Order By: Relevance
“…At regular temperatures (20 K < T < 500 K), we expect both the NC(30,150,270) and NC(90,90,270) pores to be present in single layer h-BN with pores with only trace amounts of NC(90,90,90). To the best of our knowledge, previous studies have only identified NC(90,90,90) [25,[44][45][46]. Although no probing of the local magnetism of edges or pores in h-BN has been reported, ferromagnetism has been shown to occur in h-BN at room temperature [47], which can be attributed to the existence of edges and pores in regular h-BN samples.…”
Section: A Nanopores In Monolayer H-bnmentioning
confidence: 86%
See 3 more Smart Citations
“…At regular temperatures (20 K < T < 500 K), we expect both the NC(30,150,270) and NC(90,90,270) pores to be present in single layer h-BN with pores with only trace amounts of NC(90,90,90). To the best of our knowledge, previous studies have only identified NC(90,90,90) [25,[44][45][46]. Although no probing of the local magnetism of edges or pores in h-BN has been reported, ferromagnetism has been shown to occur in h-BN at room temperature [47], which can be attributed to the existence of edges and pores in regular h-BN samples.…”
Section: A Nanopores In Monolayer H-bnmentioning
confidence: 86%
“…In the common AA -h-BN, consecutive layers are rotated by 60 • with respect to each other, and triangular pores do not neatly align. In contrast, multilayer nested pores are observed in AB-h-BN with perfectly parallel edges [15,25]. We report the geometries and electronic structures of all basic bilayer triangular pore combinations.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the atoms lining the defect are more likely to sputter than their surface counterparts for a given beam energy. As the edge atoms continue to sputter away at a high rate, the nanopore grows, eventually extending up to a few nm in diameter [9,34,35]. Cretu et al measured the radial growth of these nanopores under electron irradiation for several temperatures ranging from 673 to 1473 K [9].…”
Section: Boron and Nitrogen Sputtering From Hexagonal Boron Nitridementioning
confidence: 99%